Peran agama dalam mengatasi konflik sosial yang terjadi di masyarakat - Fudhla, Mahmudatun (Maliki Interdisciplinary Journal, 2024)
This article discusses the role of religion in overcoming social conflicts that occur in society. Social conflicts often arise due to differences in views, interests and values held by various groups in society. Religion, with its moral and ethical teachings, has great potential to become a tool for unifying and resolving conflict. This research takes various cases where the role of religion has been effective in reconciling conflicting parties and restoring social harmony. Through the research library method, data is collected from various literature sources. The results show that religion functions as an effective mediator in conflict by providing space for dialogue, facilitating understanding between groups, and offering solutions based on the teachings of peace and justice. Religious figures, religious institutions, and religious rituals and teachings play an important role in mediating conflict and building peace. . This article also explains some of the challenges faced in overcoming social conflict, as well as providing solutions to these problems. So, religion can be a constructive force in building a peaceful and harmonious society if it is applied wisely and inclusively.